Feasibility of using a patient‐reported outcome measure into clinical practice following pediatric liver transplantation: The Starzl Network experience. (22nd October 2022) - Ng, Vicky Lee; Dunphy, Claire; Shemesh, Eyal; Lobritto, Steven; Eisenberg, Elizabeth; Pomponi, Claudia; Szolna, Jonathan; Wilkerson, Dawn; Gupta, Nitika; Romero, Rene; Perito, Emily R.; DiPaola, Frank; et al.
Abstract: Background: Patient‐reported outcome measures (PROMs) are not routinely used in clinical care by pediatric liver transplant (LT) teams. The Starzl Network for Excellence in Pediatric Transplantation (SNEPT) assessed feasibility of using a disease‐specific Quality of Life (QoL) questionnaire in the ambulatory setting at 10 SNEPT sites. Methods: A mixed methods feasibility project assessing administration processes, barriers, and user experiences with the Pediatric Liver Transplant Quality of Life (PeLTQL) tool. Iterative processes sought stakeholder feedback across four phases (Pilot, Extended Pilot, Development of a Mobile App PeLTQL version, and Pilot App use). Results: A total of 149 patient–parent dyads completed the PeLTQL during LT clinic follow‐up. Clinicians, parents, and patients evaluated and reported on feasibility of operationalization. Only two of 10 SNEPT sites continued PeLTQL administration after the initial two pilot phases. Reasons include limited clinical time and available personnel aggravated by the COVID‐19 pandemic. In response, a mobile application version of the PeLTQL was initiated. Providing PeLTQL responses electronically was "very easy" or "easy" as reported by 96% (22/23) parents. Conclusions: Administration of a PROM into post‐pediatric LT clinical care was feasible, but ongoing utilization stalled. Use of a mobile app towards facilitating completion of the PeLTQL outside of clinic hours may address the time and work‐flow barriers identified.